Although tuna fisheries have significant role on Indonesian fisheries, concept for integrated tuna fisheries development in South Java Waters have not been implemented yet. This study was aimed to design model for tuna fisheries development in South Java Waters. Because of fisheries is a complex system, therefore the system approach was applied in this study. The system design, named SIMPENA model, consist of three submodels, there are (1) fisheries business (USAHA), (2) fishing port requirem - Tri Wiji Nurani; John Haluan; Sudirman Saad; Ernani Lubis (Forum Pasca Sarjana, 2008)
Although tuna fisheries have significant role on Indonesian fisheries, concept for integrated tuna fisheries development in South Java Waters have not been implemented yet.  This study was aimed to design model for tuna fisheries development in South Java Waters.  Because of fisheries is a complex system, therefore the system approach was applied in this study.  The system design, named SIMPENA model, consist of three submodels, there are (1) fisheries business (USAHA), (2) fishing port requirement: functionality and accessibility (PELABUHAN), and (3) policy and institution (LEMBAGA).  The result of this study indicated that the tuna business is a very high risk business.  Government policies which contribute a little support to the business cause a big impact for the business continuity.  There is only a few number of fishing port that could support the tuna business in this region, namely PPS Cilacap and PPN Palabuhanratu.  The development strategic analysis by using interpretative structural modeling technique resulted seven elements which playing an important role for succeeded the system.   Key words: system design, development, fisheries, tuna, South Java Waters